Design principles for rapid folding of knotted DNA nanostructures - Vid Kočar (Nature Portfolio, 2016)
Driven by complementary base pairing, artificial single-chain DNA is capable of forming complex 3D architectures if an appropriate folding pathway can be realised. Here, the authors describe the design principles for rapidly folding structures, exemplified through fabrication of a nanosized square pyramid.